The Challenge of Counterfeit Drugs in Indian Market: A Comprehensive Review - Khangan, Vikram Rameshrao; Tiple, Rupali Hemant (Indian Journal of Pharmacy Practice)
India has become a major producer and exporter of medicines and drugs, the quality of pharmaceuticals produced here and the country’s regulatory frameworks are crucial for both India and the rest of the globe. The objective of this review was to study the use of blockchain technology to offer a novel countermeasure against fake medications. The suggested approach seeks to effectively detect and prevent the distribution and consumption of counterfeit pharmaceuticals through the establishment of a transparent and secure health data network. The sale of fake and counterfeit medications in India has been linked to a number of causes, including the high cost of medications, restricted access to healthcare, and a general lack of public awareness. According to a survey, between 12 and 25% of all pharmaceuticals supplied in India are believed to be fake. India has a sizable market for spurious and counterfeit medications in addition to being one of the world’s top producers of such products. Drug counterfeiting is a threat to society that needs to be vigorously combated. Different nations have different regulations to detect drug counterfeiting, but in order to enforce these; laws, regulatory monitoring and periodic sample testing to verify the accuracy of label claims are necessary. Drug counterfeiting is now a global issue. No nation has the ability to stop the sale of fake medications in its pharmaceutical industry.
Keywords: Counterfeit Drugs; Indian Market; Pharmaceutical industry; Fake medications